The Synthesis of Integrative sustainable capability to Indonesian Sustainable Eco-print Fashion - Lufina Mahadewi; Annisa Dwiyana (Soegijapranata Catholic University, 2024)
With a focus on small businesses that are oriented towards sustainable fashion in the Eco-print business, this research focuses on forming a synthesis of Integrative Sustainable Capability variables which are derived from a systematic process through the derivation process of Resources Based Theory and Strategic Orientation. The synthesis of Strategic Resources in the theory of Resources Based and Strategic Orientation leads to the construction of a new concept, namely Integrative Sustainable Capability as a competency to integrate environmental and social considerations to strategically acquire, combine and deploy the resources in business operations and cooperation included in knowledge management to generate performance values. The structured idea process method is used to synthesize novelty constructed in the Integrative Sustainable Capability. The Integrative Sustainable Capability is used as a mediator in the relationship between Knowledge Management Capabilities and Entrepreneurial Performance in the context of Eco-print small businesses. The conceptual model was formed by linking these three variables of Knowledge Management and Entrepreneurial Performance with Integrative Sustainable Capability as a mediation derived from the synthesis of novelty process in the context of Eco-print small business.